2019
DOI: 10.1029/2018jg004932
|View full text |Cite
|
Sign up to set email alerts
|

Surface Stability in Drylands Is Influenced by Dispersal Strategy of Soil Bacteria

Abstract: Microbial adaptations for survival and dispersal may directly influence landscape stability and potential for dust emission in drylands where biological soil crusts (biocrusts) protect mineral soil surfaces from wind erosion. In the Lake Eyre basin of central Australia we operated a wind tunnel on sandy soils and collected the liberated material, which was subjected to DNA sequencing to identify the microbial community composition. Microbial composition of entrained dust was compared with that of the source sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Their greater abundance in dust might suggest an association between the potential for dust dispersal and shifts along the copiotroph/oligotroph continuum, as previously suggested by Elliott et al . (2019). For Fungi, we observed an increase in Dothideomycetes and a decrease in Sordariomycetes with decreasing particle size (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their greater abundance in dust might suggest an association between the potential for dust dispersal and shifts along the copiotroph/oligotroph continuum, as previously suggested by Elliott et al . (2019). For Fungi, we observed an increase in Dothideomycetes and a decrease in Sordariomycetes with decreasing particle size (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3C). These genera have been reported as members of fugitive dust (Elliott et al ., 2019), members of dust and airborne communities worldwide (Weon et al ., 2008; Fahlgren et al ., 2011; Favet et al ., 2013; Itani and Smith, 2016; Behzad et al ., 2018; Marizcurrena et al ., 2019), and associated with stress resistance (Denner et al ., 2006; Marizcurrena et al ., 2019; Li et al ., 2020a). ASVs related to Rubellimicrobium , as well as members of genera like Blastococcus and Geodermatophilus , were found differentially more abundant also in all dust sampling types (WT and LP) compared to soil (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dispersal routes include aerial movement from wind and rain ( Bottos et al, 2014 ) or active movement through the soil matrix ( Yang and van Elsas, 2018 ), with both likely happening in our system. Microbial cells can be transported via wind-blown dust at local and regional scales, with distance traveled dependent on wind direction, speed, and soil type ( Sabacká et al, 2012 ; Acosta-Martínez et al, 2015 ; Elliott et al, 2019 ). The Great Plains are persistently windy, so it would not be unexpected for aeolian deposition to move microbes around the landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as large herbivores like bison move around the landscape, they may serve as vectors to disperse microbial cells via dung deposition. Concurrently, dispersal of microbial cells via aerial deposition and through water films in soil pores is also likely ( Finlay and Clarke, 1999 ; Bottos et al, 2014 ; Yang and van Elsas, 2018 ; Elliott et al, 2019 ), and fire and grazing could influence how readily airborne cells reach the soil, since both create bare soil patches open to aerial inputs ( Bakker et al, 2003 ; Henry et al, 2006 ). Further, fire can promote aerial dispersal of microbes, by aerosolizing viable soil microbial cells and spores ( Kobziar et al, 2018 ; Moore et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various ecological studies on the development and ecosystem functioning of BSCs have been conducted during the last three decades (Belnap and Lange, 2003;Breckle et al, 2008;Weber et al, 2016). The nexus of science related to BSCs and aerobiology strongly suggests that BSCs can become established or re-established via naturally occurring processes (Condon et al, 2020), as BSC propagules are found naturally in the atmosphere (Elliott et al, 2019), and can be transported very long distances between hemispheres, continents, and climates (Warren et al, 2019). Even after drastic disturbances, like fires, the relatively fast recovery of microorganisms can be observed (Dümig et al, 2014;Aanderud et al;Chamizo et al, 2020).…”
Section: Editorial On the Research Topic Ecological Development And Functioning Of Biological Soil Crusts After Natural And Human Disturbmentioning
confidence: 99%